Análise das práticas de sustentabilidade utilizadas na gestão da cadeia de suprimentos: pesquisa de campo no setor automotivo - Santos, Leandro Blanco dos (2012)
The environmental imbalance caused by human actions has forced the major world governments to include environmental issues on its agenda. This imbalance is a consequence of uncontrolled consumption of natural resources and the generation of waste and emissions that have intensified since the industrial revolution. Human beings have the responsibility to develop practices to minimize the impact of their activities on the environment. This work aims to identify and analyze the most valued practices of sustainability, applied by companies that are members of the automotive supply chain. The automotive sector was chosen because it has been considered as a reference in practices of quality and also because it has great influence among its suppliers, facilitating, as a result, the dissemination of sustainable practices. The method used was the literature review on the subject and a field survey with companies that are members of the automotive supply chain located in the ABC region. Data were collected using a five-point Likert questionnaire. We identified the most valued practices of sustainability, namely: avoiding or reducing the use of hazardous substances, involving suppliers in the design stages, compliance with environmental legislation, monitoring and reducing the generation of hazardous wastes and industrial effluents, monitoring and reducing consumption of natural resources, ISO 14001 certification, cooperation of suppliers for cleaner/lean production and decreasing the frequency of environmental accidents. In conjunction with sustainable practices, we identified the most relevant practices with regards to economic and operational performance of suppliers, such as the amount of products delivered on time, commitment to quality management, order fulfillment rate, costs of transport and consistency of prices with the industry average. The results can be used as a guide for further studies and contribute to enrich the literature as well.